(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Since ancient times, Central Asia has been one of the centers of handicrafts, and it was distinguished from other historical regions by the areas of carpet weaving, embroidery and similar handicrafts. Archaeological, ethnographic and written sources provide us with valuable information about specific craft schools.